MENUMBUHKAN KEMANDIRIAN ANAK USIA DINI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Handayani, Sri; Alam, Mufassirul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early childhood independence is a crucial aspect of character development that needs to be nurtured during the golden period of life (0–8 years). Modern challenges such as the dominance of digital technology, permissive parenting styles, and academic pressures hinder the growth of children’s independence. This study aims to describe the concept of Islamic education in fostering independence in early childhood. The method used is descriptive qualitative with a library research approach. Data sources were obtained from classical and modern Islamic literature, tafsir books, hadith collections, and relevant scientific journals. Content analysis techniques were employed to identify main themes related to Islamic educational values and independence. The results show that Islamic education shapes children’s independence through three approaches: a) ta’dib (habituation of manners), b) mau’izhah (advice), and c) targhīb wa tarhīb (encouragement and warning). The concept of ta’dib focuses on internalizing values through role modeling and habituation; mau’izhah addresses the emotional and affective domains of the child through advice that builds self-awareness; while targhīb wa tarhīb provides motivation and behavioral control by developing values-based incentives related to rewards and consequences.